Needs Analysis of Development Digital-Based Physical Fitness Test Application - Wahyu Indra Bayu; Herri Yusfi; Syafaruddin Syafaruddin; Al Ikhsan Al Ikhsan; Lusiana Lusiana; Kevin Waldo (Universitas Bengkulu, 2021)
This article aims to describe a needs analysis related to the development of a digital-based physical fitness test application. This physical fitness test application will later help physical education teachers to be able to evaluate the physical fitness of students. The target respondents in this study were students and physical education teachers in South Sumatra. The results showed that, from 115 respondents who filled out questionnaires distributed online via google form, it showed that 105 (91.30%) respondents had done physical fitness tests to students, 3 (2.61%) respondents had never, and 7 (6.09%) respondents answered maybe. And 103 (89.57%) respondents want the development of test and measurement applications related to physical fitness, 2 (1.74%) respondents think “no”, and 10 (8.70%) respondents think